SCIENTIFIC ARTICLE: RENAL VASCULAR PHYSIOLOGY AND HISTOLOGY (Modern education and development, 2025)
The kidney plays a central role in blood filtration, fluid balance, and blood pressure regulation. Its vascular network is uniquely adapted to support these functions. This paper reviews the renal vascular system's physiological control mechanisms and histological organization, emphasizing the structural-functional relationships essential for homeostasis.